2014
DOI: 10.4187/respcare.02881
|View full text |Cite
|
Sign up to set email alerts
|

Training of Respiratory Muscles in Patients With Multiple Sclerosis: A Systematic Review

Abstract: BACKGROUND: The aim of this systematic review was to summarize the level of evidence and grades of recommendation regarding therapeutic respiratory muscle training interventions in patients with multiple sclerosis (MS). METHODS: We conducted a search using a number of electronic databases, and the limits of the search were studies published between 1993 and 2013. The selected documents were classified according to grades of recommendation of the Finnish Medical Society Duodecim. The methodological quality of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 27 publications
(76 reference statements)
3
24
1
Order By: Relevance
“…Several RCT studies reported approximately 20%–30% increases in MEP after six to 12 weeks of EMST training in individuals with MS. 9,10,19 We found a greater than 20% increase in MEP in our MS patients after five weeks of training, which is consistent with the published data.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several RCT studies reported approximately 20%–30% increases in MEP after six to 12 weeks of EMST training in individuals with MS. 9,10,19 We found a greater than 20% increase in MEP in our MS patients after five weeks of training, which is consistent with the published data.…”
Section: Discussionsupporting
confidence: 92%
“…7 Previous investigations have examined expiratory and inspiratory muscle strength training in MS patients regarding expiratory muscle strength training (EMST) benefits for maximum expiratory pressure (MEP) and speech, and the results were mixed. 410 One notable reason for different results could be that some studies used a device that featured progressive increase in resistance associated with practice performance, while others did not. Therefore, our first purpose was to use an EMST training device that could modulate training difficulty, according to practice performance, to evaluate effects of the EMST on respiratory function in individuals with MS.…”
Section: Ms and Respirationmentioning
confidence: 99%
“…It has been observed that respiratory muscle training can improve respiratory muscle strength (P I max ) and inspiratory muscle endurance (IME) in this population. These findings support the benefits found in subjects with multiple sclerosis 24 and COPD. 25 In addition, 3 cross-sectional studies were found [19][20][21] recommending the inclusion of respiratory muscle training in the PR program for subjects after stroke.…”
Section: Discussionsupporting
confidence: 88%
“…It follows that non-disease specific interventions capable of increasing the pressure generating capacity of the diaphragm may have important clinical and pathophysiological implications. With the exception of inspiratory muscle training (Budweiser et al, 2006; Geddes et al, 2008; Moodie et al, 2011; Berlowitz and Tamplin, 2013; Smart et al, 2013; Martin-Valero et al, 2014) and the Ca 2+ sensitizing agent, Levosimendan (van Hees et al, 2009; Doorduin et al, 2012), few generalized interventions exist to improve the force generating capacity of the human diaphragm.…”
Section: Introductionmentioning
confidence: 99%